2009
DOI: 10.1007/s12393-009-9012-6
|View full text |Cite
|
Sign up to set email alerts
|

Nanoencapsulation: A New Trend in Food Engineering Processing

Abstract: Nanoencapsulation is defined as a technology to pack substances in miniature making use of techniques such as nanocomposite, nanoemulsification, and nanoestructuration. It provides final product functionality (including controlled release of the core) which is expected to be maintained during storage. Within the food engineering field, protection of bioactive compounds such as vitamins, antioxidants, proteins, and lipids as well as carbohydrates may be achieved using this technique for the production of functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(64 citation statements)
references
References 80 publications
(82 reference statements)
0
47
0
7
Order By: Relevance
“…From days, nanotechnology rapidly occurred as one of the best encouraging research fields, with applications in health industries reported that food Industry could be have benefits from nanotechnology applications because this technology has potential to enhance solubility and bioavailability of different functional ingredients such as the "carotenoids" [55][56][57][58][59][60].…”
Section: Carotenoids As Fortified Substances In Food Industrymentioning
confidence: 99%
“…From days, nanotechnology rapidly occurred as one of the best encouraging research fields, with applications in health industries reported that food Industry could be have benefits from nanotechnology applications because this technology has potential to enhance solubility and bioavailability of different functional ingredients such as the "carotenoids" [55][56][57][58][59][60].…”
Section: Carotenoids As Fortified Substances In Food Industrymentioning
confidence: 99%
“…Vislumbra-se que a nanotecnologia faz parte de um conjunto de tecnologias que conformarão a próxima revolução tecnológica (Renn & Roco, 2006;MCT, 2010;Gordon, 2010;Peixoto, 2013).…”
Section: Nanotecnologiaunclassified
“…Também denominado de nanoencapsulação, esse processo promove a liberação controlada do produto final que pode ser uma vitamina, um antioxidante, proteínas, lipídios e hidratos de carbono. Com a liberação controlada, o produto mantém-se por mais tempo no organismo, com maior funcionalidade e estabilidade (Quintanilla-Carvajal et al, 2010).…”
Section: Clusters Pelo Agrupamento De Palavras No Período 2010-2013unclassified
“…Con el fin de incorporar sustancias bioactivas a alimentos a través de técnicas nanotecnológicas, el proceso de encapsulación presenta gran potencial para el desarrollo de productos innovadores en la industria alimentaria (Sekhon, 2010). Al atrapar un bioactivo dentro de un núcleo encapsulante se lo protege de posibles condiciones adversas (pH, luz, temperatura, humedad u oxígeno), preservando su funcionalidad, aumentando su vida útil y posibilitando su transporte (Tavares, et al, 2014;Quintanilla-Carvajal, et al, 2010).…”
Section: Introductionunclassified